Stunting prevention using a therapeutic communication model: Steps and challenges - Agustinah , Aminah; Andriani, Astri; Muchtar , Khoiruddin (Jurnal Komunikasi, 2025)
The aim of this research is to determine the communication model for stunting prevention in Sukanagalih Village. Sukanagalih Village itself is one of the priority villages in Cianjur Regency which has a stunting prevalence of 16.34 percent with 327 children under five stunting from 910 families at risk. This condition has received intervention from various parties, especially in the form of additional food assistance, monitoring and outreach from the Health Service. However, in the field the interventions carried out are considered ineffective and have not contributed to a significant reduction in prevalence. This phenomenon is then explored with descriptive qualitative research which will describe the community and its habits in understanding the concept of stunting, Sundanese culture and habits in terms of parenting, food and health. Then combined with communication patterns related to the socialization of Stunting Prevention. The research results show that the stunting prevention communication model in Sukanagalih Village uses a therapeutic communication model with 4 supporting dimensions: people, purpose, place, and process.